Device Characteristics and Capabilities Discovery for Multimedia Content - Mohd Faisal Ibrahim; Saadiah Yahya; Mohd Nasir Taib (Journal of Computer Networks and Communications)
The rapid growth of web and mobile technologies has allowed people to access multimedia content from a wide range of heterogeneous client devices that have different characteristics and capabilities. In order to deliver the best presentation of content requested, the web system must possess a mechanism that is able to accurately discover the characteristics and capabilities of a client’s device. Existing content negotiation techniques mainly focus on static profiling approach without considering the combination of static and dynamic approaches that are capable of overcoming the device scalability issues. In view of these issues, we propose a hybrid approach for recognizing devices and their capabilities using token-based method. By proposing such solution, we can provide flexible, extensible, and scalable method that provides more accurate information in resolving the content negotiation issues. To validate the effectiveness of the proposed method, we construct a laboratory and field studies to investigate its performance and accuracy. The experimental results show that the proposed hybrid approach has better performances in several aspects compared to the static profiling.